International capital mobility in West Africa: A panel cointegration approach - Ibrahim Bakari Hassan (Cogent Economics & Finance, 2016)
The study investigates the status of international capital mobility in West Africa using the saving retention coefficient of Feldstein-Horioka hypothesis. The hypothesis is predicated on the fact that, with perfect capital mobility, domestic investment does not depends on domestic savings but depends on the pool of international savings. Panel data on domestic savings and domestic investments of 13 West African countries, spanning from 1980 to 2011 are used to run a series of long-run relations. After establishing the presence of cointegration relationship between the two variables, the saving retention coefficient is estimated using the pooled mean group (PMG), fully modified OLS (FMOLS) and the dynamic OLS (DOLS). The results from these long-run estimators show low value of saving retention coefficient, signifying low association between domestic savings and domestic investment and hence higher capital mobility in West Africa. The result also confirmed that the Feldstein-Horioka puzzle does not hold for West Africa. However, the presence of free and higher capital mobility in the continent could be a signal that the use of monetary policy in domestic economic stabilization is increasingly becoming ineffective, especially in the long-run. The finding suggests the establishment of monetary union in the region.
Keywords: 330; saving retention coefficient; domestic investment; domestic savings international capital mobility; panel cointegration